Prospective methodologies to use impact wear for micro/nano finishing of surfaces. (1st January 2014) - Sooraj, V.S.; Radhakrishnan, V.
Impact erosion using abrasive particles is used for material removal in many manufacturing processes. Abrasive jet machining and abrasive water jet machining are classic examples for this. In these processes, the erosion is severe due to high velocity impact of the particles. However, if the impact velocity is low the erosion can be regulated to achieve fine finishing of surfaces. In this paper, regulated surface erosion through low velocity elastic impact of abrasives is analysed and studied through experimentation. Detailed experimental investigations, using carrier type fluidisation of abrasive particles, have demonstrated that the finish can be substantially improved by this procedure.